2022
DOI: 10.1111/jcpp.13673
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary screen time modalities and disruptive behavior disorders in children: a prospective cohort study

Abstract: Background: Cross-sectional studies have demonstrated associations between screen time and disruptive behavior disorders (conduct disorder and oppositional defiant disorder); however, prospective associations remain unknown. This study's objective was to determine the prospective associations of contemporary screen time modalities with conduct and oppositional defiant disorder in a national cohort of 9-11-year-old children. Methods: We analyzed data from the Adolescent Brain Cognitive Development (ABCD) Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 74 publications
1
12
0
1
Order By: Relevance
“…We have previously shown that greater screen time is associated with higher BMI percentile in the ABCD Study [ 19 , 50 ]. In addition, contemporary screen modalities (e.g., social media, video games) may lead to exposure to cyberbullying, violence, or other stressful content that could raise blood pressure [ 32 , 51 ]. These mechanisms may explain why high screen time may be associated with poorer cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that greater screen time is associated with higher BMI percentile in the ABCD Study [ 19 , 50 ]. In addition, contemporary screen modalities (e.g., social media, video games) may lead to exposure to cyberbullying, violence, or other stressful content that could raise blood pressure [ 32 , 51 ]. These mechanisms may explain why high screen time may be associated with poorer cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Screen time was calculated as a continuous variable and categorized into four-hour increments. This categorization was based on prior studies identifying four hours per day to be a threshold linked to poor mental health outcomes and overweight in adolescents [ 30 32 ], and other national surveys of adolescent screen time have used similar categories (e.g., 4 and 8 h per day) with similar distributions [ 19 , 33 ]. Screen time (hours per day) was ordered into three categories: 0 to 4 h (low; reference category), 4 to 8 h (medium), and more than 8 h (high).…”
Section: Methodsmentioning
confidence: 99%
“…Similar self-reported television-watching measures have had acceptable test-retest reliability (7-day test-retest intraclass correlations of 0.76-0.81). 17,18 We categorized total recreational screen time in 4-hour increments given that previous studies have identified 4 hours per day to be a threshold associated with overweight and poor mental health outcomes in adolescent populations, [19][20][21][22] and other nationally representative surveys of adolescent screen time have used similar categories (ie, 4 hours per day and 8 hours per day). 23 Screen time was grouped into 3 categories: 0 hours to 4 hours per day (low; reference category), more than 4 hours to 8 hours per day (medium), and more than 8 hours per day (high).…”
Section: Exposure Variables Screen Timementioning
confidence: 99%
“…In contrast, the relationship between screen use and child development is not yet well understood. The majority of studies indicate that prolonged screen use is associated with adverse effects on brain structure and function [19][20][21] , as well as cognitive and behavioral problems 9,10,22 . One possible explanation for the negative effects of screen use is the displacement hypothesis 5 , which suggests that screen time and other activities compete for leisure time and that longer screen time may reduce other leisure activities, such as exercise and reading 5,23 .…”
Section: Introductionmentioning
confidence: 99%